Merck & Co : after Vioxx, the government and the pharmaceutical industry reconsider the balance between innovation, safety, and cost - Elias, Jaan, (SAGE knowledge. Cases., 2016)
Merck & Co. had built an enviable reputation not just as a paragon of the pharmaceutical industry but as one of America's most admired businesses. The company had produced medical breakthrough after medical breakthrough, engaged in extensive philanthropy, and instituted progressive human resources policies, all the while delivering stellar financial performance. And yet, after withdrawing its blockbuster drug Vioxx in September of 2004, Merck found its reputation and its financial stability in danger. This case examines the challenges that faced Merck in the wake of the Vioxx recall.